(untitled) - Watanabe, Toshio (Japan, 1992)
Contents: Race against population growth, economic development and birth rate, polarization of the peasantry, changes and conflicts in the traditional socirty,...
Keywords: Asia,Châu Á; Economic condions,Điều kiện kinh tế; 1945-,1945-